The books of Haggai and Malachi - Jacobs, Mignon R. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2017)
In this commentary on Haggai and Malachi, Mignon Jacobs offers clear and insightful interpretation of the text while highlighting themes that are especially relevant to contemporary concerns, such as honoring or dishonoring God, the responsibilities of leaders, questioning God, and hearing the prophetic word in challenging times. Engaging with the latest scholarship, Jacobs provides a thorough introduction to both prophets in which she addresses questions of authorship, date, purpose, structure, and theology, followed by a new translation of the biblical text and a verse-by-verse commentary. With intertextual discussions about key aspects of the text and attention to competing perspectives, this commentary offers a rich new interpretation of Haggai and Malachi. - from publisher.
The book of Haggai -- Prophet and date -- Historical context -- Text -- Intertextual indicators -- Structural analysis -- Message -- Text and commentary -- Disputation sequence about building the temple (1:2-15) -- Encouragement: inquiry and admonition (2:1-9) -- Oracle concerning a new era (2:10-23) -- The book of Malachi -- Historical context -- Text -- Intertextual indicators -- Structural analysis -- Message -- Text and commentary -- Introduction: disputation regarding Yahweh's love for Israel (1:2-5) -- Disputation sequence: behaviors and beliefs regarding honor (1:6--2:16) -- Disputation sequence: words exemplifying beliefs (2:17--4:6 [MT 2:17--3:24]).
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries